Konsep dan Etika Kebahagiaan Melalui Ekonomi Sufistik - Casmini casmini (WELFARE : Jurnal Ilmu Kesejahteraan Sosial, 2022)
This article aims to describe the thinking about economic practices that are not dichotomous with religion to get happiness. The offer of Sufistic spirituality becomes a bridge that connects economic activity with servitude to Allah SWT. This research is a literary study with primary sources of positive psychology literature, Sufistic economics and happiness, and secondary sources in the form of complementary sources, namely data about which supports a person can be happy such as economics and Sufism practices. Data analysis was carried out with stages of identification data collection, clarification between sources, classification of discussion themes, narrating, and discussing in a systematic and coherent system. The results showed that happiness is found in the course of economic practices inspired by Sufi spiritual values. Economic practice is guided by the foundation of life that relies on spiritual feelings namely, faith, Islam and ihsan through the stages of takhalli, tahalli and tajalli to find ultimate happiness. Economic behavior runs through the integration of physical and spiritual elements which are integrated into the spirit of economic practice in people's lives. Keywords: happiness, sufistic-economic, spirituality, economic action   Artikel ini bertujuan mendeskripsikan pemikiran tentang praktik ekonomi yang tidak dikhotomis dengan agama untuk mendapatkan kebahagiaan. Tawaran spiritualitas sufistik menjadi jembatan yang menghubungkan kegiatan ekonomi dengan penghambaan kepada Allah SWT. Penelitian ini merupakan penelitian literartur dengan sumber primer literatur psikologi positif, ekonomi sufistik dan kebahagiaan, dan sumber sekunder berupa sumber komplementer yaitu data-data mengenai yang mendukung seseorang dapat bahagia seperti ekonomi dan praktik tasawuf. Analisis data dilakukan dengan tahapan pengumpulan data identifikasi, klarifikasi antar sumber, klasifikasi tema-tema bahasan dan menarasikan serta mendiskusikan dalam sistematika yang runtut dan jelas. Hasil penelitian menunjukkan bahwa kebahagiaan ditemukan seiring perjalanan praktik ekonomi yang dijiwai oleh nilai-nilai spiritualitas sufistik.  Praktik ekonomi tertuntun dengan landasan kehidupan yang bersandar pada perasaan spiritual yaitu, iman, Islam dan ihsan melalui tahapan takhalli, tahalli dan tajalli untuk menemukan kebahagiaan hakiki. Laku ekonomi berjalan melalui integrasi unsur jasmaniah dan ruhaniah yang menyatu menjadi ruh spiritualitas praktik ekonomi dalam kehidupan masyarakat. Kata Kunci: kebahagiaan, ekonomi sufistik, spiritualitas, praktik ekonomi